Assessment of the farmer's/sprayer's socio-demographic and economic profile, knowledge, perception and practices of pesticide usage in the plantations of mangoes in Sapangdaku and cutflowers in Busay, Cebu City, Central Philippines - Sentillas, Faith Bunsay
A survey was conducted among the cutflower farmers and mango sprayers in Barangays Busay and Sapangdaku to document type of pesticide being used by the farmers/pesticide applicators, document their socio-demographic and economic profile of the farmers/sprayers, determine the levels of knowledge on good application protocols, safety precautions, storage and disposal, determine levels of perception on the use and effects of pesticides on health and environment, determine practices on application, safety precautions storage and disposal of pesticide correlate socio-demographic and economic key indicators with knowledge, perception and prctices, document human health impact and to recommend improvement on management startegies already being adopted specifically by the farmer, and by the industry, in general. Results indicated that the pesticide used by farmers and pesticide applicators in Barangays Busay and and Sapangdaku were not the recommended ones. There are still farmers or pesticide applicators that are using restricted and banned pesticides and the pesticides not recommended for cutflowers and mangoes like Thiodan, Lannate and others. The socio-demographic and economic profile was normal for an agricultural sector. Majority of the farmers/pesticide applicators in the two barangays were using pesticide for thir crops such as cutflowers and mangoes and the farmer's primary source of income is production of agricultural crops. Consequently, cutflower farmers had better knowledge, different practices and lower perception towards the use and effects of pesticides to humans and to the environement. The farmer/pesticide applicators in Barangays Busay and Sapangdaku were highly knowledgeable in terms of good application protocols and safety precaution, storage and disposal. From the findings of the study, it was found out that there is correlation between socio-demographic and economic key indicators with knowledge and practice on good application protocols and safelty precaution, storage and disposal and perception on the effects of pesticides on health and the environment. Based on the information from the farmers/pesticide applicators, there is human health impact. Furthermore, most of the farmers in the two barangays were not adopting alternatives to pesticide and a few farmers adopted IPM. There should be proper monitoring on the type of pesticides and volumes of pesticides used by farmers. In addition, the farmers/pesticide applicators should be regularly reminded of the hazardous nature of pesticides and also health conditions of the farmers/pesticide applicators should be monitored. At the LGU Levels, there should be ordinances on the stringent prohibition of unsafe disposal of pesticide leftover and empty pesticide containers. Furthermore, there should be massive and more intensified information campaign through various agricultural programs for farmers on the proper and safe use of pesticides.